Expression of NLRP3 inflammasome in leprosy indicates immune evasion of Mycobacterium leprae - Ana Luisa Gomes Mendes; Heloísa Di Matteo Joaquim; Mara Inês Stefanini Zamae; Ramon Meira Assis; Jéssica Renata de Moura Peixoto; Margarida Maria Gomes de Araújo; Antônio Carlos Martins Guedes; Edward José Oliveira; Vanessa Peruhype Magalhães; Marcelo Antônio Pascoal-Xavier (Memorias do Instituto Oswaldo Cruz, 2020)
BACKGROUND Leprosy is an infectious-contagious disease caused by Mycobacterium leprae that remain endemic in 105 countries. This neglected disease has a wide range of clinical and histopathological manifestations that are related to the host inflammatory and immune responses. More recently, the inflammasome has assumed a relevant role in the inflammatory response against microbiological agents. However, the involvement of inflammasome in leprosy remains poorly understood. OBJECTIVES The aim is to associate biomarkers of inflammasome with the different immunopathological forms of leprosy. METHODS We performed an observational, cross-sectional, and comparative study of the immunophenotypic expression of inflammasome-associated proteins in immunopathological forms of leprosy of 99 skin lesion samples by immunohistochemistry. The intensity and percentage of NLRP3, Caspase-1, Caspases-4/5, interleukin-1β and interleukin-18 immunoreactivities in the inflammatory infiltrate of skin biopsies were evaluated. FINDINGS Strong expression of NLRP3 and inflammatory Caspases-4/5 were observed in lepromatous leprosy (lepromatous pole). In addition, were observed low expression of caspase-1, interleukin-1β, and interleukin-18 in tuberculoid and lepromatous leprosy. The interpolar or borderline form showed immunophenotype predominantly similar to the lepromatous pole. MAIN CONCLUSIONS Our results demonstrate that the NLRP3 inflammasome is inactive in leprosy, suggesting immune evasion of M. leprae.